A comparison of professionals' and patients' understanding of asthma: evidence of emerging dualities?. Issue 1 (1st June 2001) - Sweeney, K G; Edwards, Karen; Stead, Jonathan; Halpin, David
Abstract : Despite an increase in the provision of services to patients with asthma, morbidity from the disease remains high. Recent research (outside asthma) has raised the possibility that patients may develop a conceptualisation of illnesses which is not entirely compatible with the prevailing biomedical view. This paper compares the way in which health care professionals and patients with asthma described various aspects of the illness, using an approach which considered the type of knowledge which might be used to construct the respective conceptualisations of asthma. A qualitative method is empliyed, using focus groups. Eight focus groups were convened, four of professionals and four of patients with asthma. Following the initial data analysis, the results were reviewed linguistically, with particular attention to the use of metaphor. The health care professionals and patients participating in this study agreed broadly in their explanations of the aetiology and drug treatment of asthma. The data suggest lack of congruence in the development of treatment strategies and locus of control. Health care professionals and patients in this study used linguistically different metaphors to represent the disease: the former more frequently used metaphors evoking on-going processes, the latter visualising the chest (in their use of metaphor) as a static container, emptying and filling throughout the course of the disease. Two commentaries from philosophical and anthropological literature are considered in order to offer theoretical accounts relevant to this interpretation. The data suggest an emerging duality in the approach to treatment plans, in the roles played by professionals and patients with asthma, and in the different types of knowledge used by professionals and patients to construct their respective working models of asthma.